1979
DOI: 10.1182/blood.v54.6.1347.bloodjournal5461347
|View full text |Cite
|
Sign up to set email alerts
|

Willebrand factor in hemostasis in the in vitro bleeding time

Abstract: Heparinized porcine blood and plasma, at constant hydrostatic pressure, was allowed to flow through a 5-mm incision in a small piece of porcine skin. Changes in the exuded blood volume were measured, and the incision site was examined microscopically. When normal blood flowed through either normal or von Willebrand skin, the exuded blood volume decreased gradually and eventually stopped. Microscopic examination revealed a platelet plug in the incision site. This plug was positive for Willebrand factor when exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These workers labelled platelets and Willebrand factor radioactively and their study suggested that Willebrand factor bound to the subendo thelium induced platelet adhesion and that it was the plasma protein alone that was necessary for normal platelet adhesion. Recent work in our own laboratory, with the use of a porcine system, is entirely consistent with these results (Bowie et al 1978;Kimura et al 1979).…”
Section: Studies In Humanssupporting
confidence: 79%
See 2 more Smart Citations
“…These workers labelled platelets and Willebrand factor radioactively and their study suggested that Willebrand factor bound to the subendo thelium induced platelet adhesion and that it was the plasma protein alone that was necessary for normal platelet adhesion. Recent work in our own laboratory, with the use of a porcine system, is entirely consistent with these results (Bowie et al 1978;Kimura et al 1979).…”
Section: Studies In Humanssupporting
confidence: 79%
“…This platelet -arterial wall interaction is enhanced by the von Willebrand factor in the plasma (Fass et al 1976a;Bowie et al 1978), platelets and the arterial wall (Jaffe et al 1974). The earlier discussion of our studies with the use of transfusions and in vitro bleeding time technique suggests that the level of Willebrand factor in the plasma plays an important role in this platelet -blood vessel interaction Kimura et al 1979). There is also evidence that adherence of platelets to the arterial surface in the normal animal may help to repair the endothelium and reduce its permeability (Gimbrone et al 1969;Wojcik et al 1969;Fry et al 1976;Reidy & Bowyer 1977).…”
Section: R Esistance To Atherosclerosis In Porcine Von W Illebrand's Diseasementioning
confidence: 79%
See 1 more Smart Citation